Analisis Biaya Produksi Dan Biaya Pemasaran Terhadap Biaya Volume Laba (Cvp) Studi Kasus Pada Marketplace Krupuk Kulit Anugrah - Irine Mei Hapsari; Saptantinah, Dewi (Nirta Learning Centre, 2025)
. This study analyzes the effect of production and marketing costs on the profitability of the Krupuk Kulit Anugrah business on the Shopee marketplace, focusing on the relationship between costs, sales volume, and profit. In the context of digital transformation, information technology plays an important role in market segmentation and marketing strategies, but many businesses have difficulty managing costs and profits. Cost Volume Profit (CVP) analysis was used to determine break-even points and profit targets, with results showing that high production costs (Rp186,745,000 per month) reduce profit margins, while fluctuations in monthly turnover (Rp175,750,000 to Rp250,600,000) are influenced by marketing strategies such as the use of Shopee's Live feature and Flash Sale. This research emphasizes the importance of cost efficiency and appropriate marketing strategies to improve profitability and business sustainability in a competitive market.